Analisis Pengelolaan Desa Pajambon Kecamatan Karyamulya Kabupaten Kuningan Sebagai Desa Ekowisata - Dian Permana Putri (Universitas Sebelas Maret, 2016)
The purpose of this study is to know the envirometal condition an potentials of Pajambon village and to compile ideal strategy management for Pajambon village as an eco tourism village. The method of this study that being used are quantitatif and qualitative approach to identify potentials in study location. The analysis that being used was SWOT analysis to compile some recommendations that useful in a village management as an eco tourism village. The analysis show that Pajambon village has some interesting natural potentials. That can be develop to be an interesting eco tourism village . Some Natural potentials in Pajambon are guava plantation garden that grows on beautiful valley of ciremai mountain, waterfals,camping ground, animals watching, hot spring water resources that located near by the waterfall, and Pajambon village also has hidrology potential that not only use as tourism and agriculture needs but also used to make and meet the household needs for people around Pajambon. Historical site also found in Pajambon. That called “pangeran arya kamuning site”(well known as the founder of Kuningan City / the first king of Kuningan) is located by the border of Pajambon village and national park area of mountain Ciremai. Ciremai mountain and people of Pajambon village will support Pajambon village to be eco tourism village. According to SWOT analysis report we recommend 1) improvement of infrastructure and improvement of processing waste system as well as improvement of tourism bussines, 2) Train people how to planning, managing, and marketing of natural resourses that can be sold as an eco tourism village, 3) Dig the potentials of people to be community tourism awareness, 4) Continue analysis the impact of environmental change for eco tourism business in Pajambon.